EXAMINATIONS OF IMPACTS OF EMPOWERING LEADERSHIP ON INNOVATION ACTIVITIES IN SERVICE SECTOR AND EMPLOYEES - GÜÇLENDİRİCİ LİDERLİĞİN, HİZMET SEKTÖRÜNDEKİ YENİLİK FAALİYETLERİNE VE ÇALIŞANLARA ETKİLERİNİN İNCELENMESİ - Zafer Adıgüzel; Yeliz Cayan (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The organizations in service sector in intensecompetition environment fall behind as a result of not showing performance indesired level and have to leave from the sector. In terms of leadership styles,it is necessary to manage the satisfaction and team management with the rightunderstanding in the superior-subordinate relationship hierarchy of theorganizations. By managing and guiding employees correctly, organizations canachieve their goals that they set. The research model examines how institutionsin the service sector affect employees and innovation through the empoweringinfluence of leadership. When the findings are analyzed, it was found thatempowering leadership and proactive personality variables had positive effectson career satisfaction, innovation and creativity activities. Within the scopeof the study, survey were conducted with 483 white-collar workers (administrativepersonnel) who work in the service sector. IBM SPSS 25 Statistical SoftwareProgram and SPSS AMOS were used to make analysis. Since there were 5-pointLikert-scale questions in the study, confirmatory and explanatory factoranalysis was conducted. After factor analysis, reliability analysis,correlation analysis, regression analysis, and Sobel test was made for theanalysis of hypothesis and regression analysis.